Involvement of community pharmacists in public health priorities: A multi-center descriptive survey in Ethiopia. - Daniel Asfaw Erku (PLoS ONE, 2017)
Located in the heart of the community and widely distributed geographically, community pharmacies provide a platform for a more proactive involvement in public health services. So far, little information has been gathered in Ethiopia on community pharmacists' level of involvement in public health services. The aim of the present study was, therefore, to document the level of involvement of community pharmacy professionals in the provision of public health services and the barriers to such involvement. This study employed a self-administered questionnaire based survey, which asked participants to indicate their frequency and level of involvement in providing public health services and their perceived barriers in providing such services. Surveys were undertaken from May to July, 2016 with 472 community pharmacy professionals working in community pharmacies in six cities of Amhara regional state of Ethiopia: Debre Markos, Gondar, Dessie, Bahir Dar, Woldya and Debre Birhan. Among 472 community pharmacy professionals approached, 412 (233 pharmacists and 179 pharmacy technicians) completed the survey with a response rate of 87.3%. Most respondents reported as being either "not at all involved" or "little involved" in counselling on smoking cessation (79.3%), and screening for hypertension (86.9%), diabetes (89.5%), and dyslipidemia (88.9%). On the other hand, they reported a higher level of involvement in the management and screening of infectious diseases (72.8%) and counseling with partners when initiating treatment for sexually transmitted diseases (68.9%). Lack of knowledge or clinical skills and lack of personnel or resources were the most commonly reported barrier for expanding such services. This survey revealed a low level of involvement of community pharmacists in public health services. In order to better integrate community pharmacies into future public health programs and optimize the contribution of community pharmacy professionals, interventions should focus on overcoming the identified barriers.